Genomic imprinting mediates dosage compensation in a young plant XY system - Muyle, Aline; Zemp, Niklaus; Fruchard, Cécile; Cegan, Radim; Vrana, Jan; Deschamps, Clothilde; Tavares, Raquel; Hobza, Roman; Picard, Franck; Widmer, Alex; Marais, Gabriel A B (Nature plants, 2018)
Sex chromosomes have repeatedly evolved from a pair of autosomes. Consequently, X and Y chromosomes initially have similar gene content, but ongoing Y degeneration leads to reduced expression and eventual loss of Y genes1. The resulting imbalance in gene expression between Y genes and the rest of the genome is expected to reduce male fitness, especially when protein networks have components from both autosomes and sex chromosomes. A diverse set of dosage compensating mechanisms that alleviates these negative effects has been described in animals2-4. However, the early steps in the evolution of dosage compensation remain unknown, and dosage compensation is poorly understood in plants5. Here, we describe a dosage compensation mechanism in the evolutionarily young XY sex determination system of the plant Silene latifolia. Genomic imprinting results in higher expression from the maternal X chromosome in both males and females. This compensates for reduced Y expression in males, but results in X overexpression in females and may be detrimental. It could represent a transient early stage in the evolution of dosage compensation. Our finding has striking resemblance to the first stage proposed by Ohno6 for the evolution of X inactivation in mammals.
Keywords: pohlavní chromozomy; regulace genové exprese u rostlin; Silene; Genomic Imprinting; chromozomy rostlin; kompenzace dávky (genetika); genomový imprinting; Sex Chromosomes; Dosage Compensation, Genetic; Chromosomes, Plant; Gene Expression Regulation, Plant